Functional crosstalk between dendritic cells and Foxp3+ regulatory T cells in the maintenance of immune tolerance - Kornete, Mara; Piccirillo, Ciriaco A. (Frontiers in Immunology, 2012)
Peripheral immune tolerance requires a controlled balance between the maintenance of self-tolerance and the capacity to engage protective immune responses against pathogens. Dendritic cells (DCs) serve as sentinels of the immune system by sensing environmental and inflammatory signals, and play an essential role in the maintenance of immune tolerance. To achieve this, DC play a key role in dictating the outcome of immune responses by influencing the balance between inflammatory or Foxp3+ regulatory T (Treg) cell responses. At the heart of this immunological balance is a finely regulated DC and Treg cell crosstalk whereby Treg cells modulate DC phenotype and function, and DC drive the differentiation of Foxp3+ Treg cells in order to control immune responses. This review will focus on recent advances, which highlight the importance of this bidirectional DC and Treg cell crosstalk during the induction of tolerance and organ-specific autoimmunity. More specifically, we will discuss how Treg cells modulate DC function for the suppression of inflammatory responses and how DC subsets employ diverse mechanisms to drive differentiation of Treg cells. Finally, we will discuss the therapeutic potential of tolerogenic DCs for the induction of tolerance in autoimmune diseases.